Relationship Between Organizational Commitment Dimensions and Job Satisfaction: The Case of Employees of Sorsogon State College Bulan Cam-pus - Bongalonta, Michael B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
This study assessed the level of organizational commitment in terms of affective commitment, continuance commitment and normative commitment as well as the job satisfaction of employees of Sorsogon State College Bulan Campus (SSC-BC) to test if there is significant relationship among these variables. Descriptive correlational method of research was used. For this purpose, survey questionnaires were used to facilitate the survey. Out of the total 49 workforce, only 40 employees of SSC-BC were considered as the respondents. Descriptive and inferential statistics were used. Weighted mean was used for the purpose of summarizing, interpreting and identifying the trends and patterns of the data gathered from the survey. Pearson’s Product Moment Correlation was employed to establish the relationship between the organizational commitment of the respondents and their job satisfaction while linear regression was utilized to determine the magnitude of the relationship of the organizational commitment dimensions and the job satisfaction of the employees. Results of the survey revealed that employees of Sorsogon State College Bulan Campus were highly committed to their institution which emanates from the level of their affective and normative commitment and less from their continuance commitment. It was concluded that that faculty members and non-teaching personnel of the College have high level of job satisfaction which appeared to derive from the kind of relationship they have with their co-workers and supervisors, from College and from the work itself. Finally, the extent of employees’ affective, continuance and normative commitment have a significant and positive relationship to the level of their job satisfaction and that the level of normative commitment was found to be a predictor of level of job satisfaction of SSC-BC employees.